Respiratory care calculations - Chang, David W. (Clifton Park, New York : Delmar Cengage Learning, 2012)
Covers all essential calculations in the practice of respiratory therapy in an easy-to-read, clear, and logical format. A review of basic math functions ensures that readers have the foundational skills needed to successfully compute calculations, and the author's step-by-step approach helps the reader avoid common mistakes.
Review of basic math functions -- Respiratory care calculations -- Ventilator waveform -- Basic statistics and educational calculations -- Answer key to self-assessment questions -- Symbols and abbreviations -- Units of measurement -- Listing of appendices -- A: Anatomical values in children and adults -- B: Apgar score -- C: Barometric pressures at selected altitudes -- D: Basal metabolic rate -- E: Conversion factors for duration of gas cylinders -- F: Conversion factors from ATPS to BTPS -- G: Croup score -- H: Croup score modified Westley -- I: DuBois body surface chart -- J: Electrolyte concentrations in plasma -- K: Endotracheal tubes and suction catheters -- L: Energy expenditure, resting and total -- M: Fagerstrom nicotine dependence test for cigarette smokers -- N: French and millimeter conversions -- O: Glasgow coma score -- P: Harris Benedict formula -- Q: Hemodynamic normal ranges -- R: Humidity capacity of saturated gas at selected temperatures -- S: Logarithm table -- T: Lung volumes, capacities, and ventilation -- U: Neonatal blood pressure -- V: Oxygen transport -- W: Reference laboratory values -- X: PAO2 at selected F1O2 -- Y: Partial pressure (in mm Hg) of gases in the air, alveoli, and blood -- Z: Periodic chart of elements -- AA: Pitting edema scale -- BB: Pressure conversion table -- CC: Ramsay sedation scale -- DD: Revised sedation scale -- EE: Richmond agitation and sedation scale -- FF: Sedation agitation scale -- GG: Therapeutic blood levels of selected drugs -- HH: Weaning criteria
Includes bibliographical references and index.
Keywords: MONITORING, PHYSIOLOGIC METHODS